2005
DOI: 10.1038/sj.npp.1300845
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic and Metabotropic Glutamate Receptor Antagonism Attenuates Cue-Induced Cocaine Seeking

Abstract: Neuroanatomical and pharmacological evidence implicates glutamate transmission in drug-environment conditioning that partly controls drug seeking and relapse. Glutamate receptors could be targets for pharmacological attenuation of the motivational properties of drugpaired cues and for relapse prevention. The purpose of the present study was therefore to investigate the involvement of ionotropic and metabotropic glutamate receptor subtypes in cue-induced reinstatement of cocaine-seeking behavior. Rats were trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
121
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(135 citation statements)
references
References 50 publications
9
121
2
3
Order By: Relevance
“…Using the cue-induced reinstatement model, considered an animal model of relapse vulnerability (Shaham et al, 2003;Sanchis-Segura and Spanagel, 2006;Stephens et al, 2010), our current findings add to previous reports indicating a role of mGluR5 in regulating behavioral responses to cocaine (Chiamulera et al, 2001) and cocaine-paired cues (Bäckström and Hyytiä, 2006) by suggesting a location of mGluR5 necessary for the cue-induced reinstatement of cocaine-seeking, while the primary reinforcing effects of cocaine are unaffected following specific knock-down of mGluR5 on D1R-expressing neurons. Our study also lends mechanistic confidence to previous reports that have used pharmacological tools to identify a role of mGluR5 in behaviors maintained by reward-paired stimuli (Tessari et al, 2004;Bespalov et al, 2005;Bäckström and Hyytiä, 2006;Schroeder et al, 2008;Gass et al, 2009;Kumaresan et al, 2009;MartinFardon et al, 2009;O'Connor et al, 2010), since these reports could have reflected off-target (Olive, 2009), anhedonic (Bäckström and Hyytiä, 2007) or reinforcing (van der Kam et al, 2009) effects of the pharmacological tools used.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Using the cue-induced reinstatement model, considered an animal model of relapse vulnerability (Shaham et al, 2003;Sanchis-Segura and Spanagel, 2006;Stephens et al, 2010), our current findings add to previous reports indicating a role of mGluR5 in regulating behavioral responses to cocaine (Chiamulera et al, 2001) and cocaine-paired cues (Bäckström and Hyytiä, 2006) by suggesting a location of mGluR5 necessary for the cue-induced reinstatement of cocaine-seeking, while the primary reinforcing effects of cocaine are unaffected following specific knock-down of mGluR5 on D1R-expressing neurons. Our study also lends mechanistic confidence to previous reports that have used pharmacological tools to identify a role of mGluR5 in behaviors maintained by reward-paired stimuli (Tessari et al, 2004;Bespalov et al, 2005;Bäckström and Hyytiä, 2006;Schroeder et al, 2008;Gass et al, 2009;Kumaresan et al, 2009;MartinFardon et al, 2009;O'Connor et al, 2010), since these reports could have reflected off-target (Olive, 2009), anhedonic (Bäckström and Hyytiä, 2007) or reinforcing (van der Kam et al, 2009) effects of the pharmacological tools used.…”
Section: Discussionsupporting
confidence: 74%
“…Our study also lends mechanistic confidence to previous reports that have used pharmacological tools to identify a role of mGluR5 in behaviors maintained by reward-paired stimuli (Tessari et al, 2004;Bespalov et al, 2005;Bäckström and Hyytiä, 2006;Schroeder et al, 2008;Gass et al, 2009;Kumaresan et al, 2009;MartinFardon et al, 2009;O'Connor et al, 2010), since these reports could have reflected off-target (Olive, 2009), anhedonic (Bäckström and Hyytiä, 2007) or reinforcing (van der Kam et al, 2009) effects of the pharmacological tools used.…”
Section: Discussionmentioning
confidence: 67%
“…Systemic administration of NMDAR antagonists inhibits the expression of cocaine-conditioned place preference and explicit cueinduced instrumental cocaine-or ethanol-seeking behaviors (Bachteler et al, 2005;Backstrom and Hyytia, 2006;Maldonado et al, 2007). These effects are mediated by NMDAR populations in multiple brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have shown that the first generation of selective full mGlu 5 NAMs, MPEP and MTEP (Gasparini et al, 1999;Cosford et al, 2003), reduced cocaine self-administration, attenuated drug and cue-mediated reinstatement of cocaine-seeking behavior, and/or blocked cocaine-induced conditioned place preference (CPP) in rodents and nonhuman primates (McGeehan and Olive, 2003;Herzig and Schmidt, 2004;Kenny et al, 2005;Lee et al, 2005;Paterson and Markou, 2005;Backstrom and Hyytia, 2006;Kumaresan et al, 2009;Brown et al, 2012). MPEP and MTEP also produced robust anxiolytic-and antidepressantlike activity, suggesting that mGlu 5 NAMs may be effective in treating the comorbid symptoms observed in cocaine addicts (Busse et al, 2004;Ballard et al, 2005).…”
Section: Introductionmentioning
confidence: 99%